The illegal trade in European eels: outsourcing, funding, and complex symbiotic-antithetical relationships - Alonso, Aitor Ibáñez (Trends in organized crime, 2023)
Whilst traditionally, the study of the illegal wildlife trade has been focused on species that consider the role of the Western world as a consumer or transit hub, the study of the illegal trade in European eels is a landmark opportunity to deem the role of Europe as a source area for wildlife trafficking. Based on a qualitative methods research design, this case study delves into the nature of the illegal trade in European eels. In the context of globalization, a global eel market developed at the same time as stocks decreased sharply. The process of criminalization of the trade and fishing of eels, in combination with criminogenic asymmetries, has been facilitating opportunities for crime groups. In the legal-illegal continuum, upper- and underworld actors interact along the chain from rivers to worldwide consumers. This constant interaction fuels the illegal trade by providing the underworld with vital elements for its continuity, such as protection, finance, or laundering. In particular, this research focusses on the different legal-illegal interactions by looking at outsourcing, funding and complex symbiotic-antithetical relationships.